Memahami konsep persaudaraan dan persahabatan dalam Ritual Bu’a Bazar dan relevansinya dengan Ensiklik Fratelli Tutti - Yohanes Hego Mukin; Benedikta Yosefina Kebingin; Yosep Belen Keban (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
Cultural ritual as a manifestation of human action to live in harmony within the bonds of norms and values contained in the ritual carried out by society. One of them is the Bu'a Bazar ritual which is still carried out in the life of the Lewobele adat community. This study aims to determine the understanding of the Lewobele adat community about the concept of brotherhood and friendship in the Bu'a Bazar ritual and its relevance to the Encyclical Fratelli Tutti. The research method used is qualitative method with a descriptive approach. Data collection through interviews, observation, and documentation. The results of this study found that the Bu'a Bazar ritual contains meanings that are contained as a concept of brotherhood and friendship, namely; (1) Attitude of mutual respect and appreciation, seen in the meaning of Ede Howek, and Hape Manuk, not only in relation to God but also in interpersonal relationships in society. (2) Supporting unity, which is seen in the meaning of toto dulak, bu'a mukang, and gelia mei because community members actively participate in its implementation, strengthening community ties and solidarity. As a sign of strong brotherhood and friendship. (3) Emphasizing justice, reflected in the meaning of napa muko lolo and bu'a mukang which treats individuals with the same dignity and honor, guided by rational and moral principles. This is fair in distributing food evenly without any differences and loving each other as fellow beings who are just.